Determinación de los parámetros físico, químicos y biológicos del agua de consumo humano del barrio Cuatro Esquinas parroquia Eloy Alfaro cantón Latacunga, provincia de Cotopaxi en el periodo 2013 - Barahona Jami, Segundo Ignacio (2014)
This study consisted of an analysis of the physical, chemical and biological parameters of water for human consumption on the neighborhood Cuatro Esquinas, Eloy Alfaro parish, Latacunga city, Cotopaxi province, period 2013. There were four points of measurements, one is the tank of arrival water , settling tanks and distribution network of the municipal water treatment plant " Loma de Alcoceres " and at other point was the house of Mr. Carlos Herrera. The results concluded: the total dissolved solids ( 63mg / l) , color (15 Upt co) and turbidity ( 5NTU ) recorded in the four measurement points do not exceed the maximum permissible limit for drinking water remained at acceptable levels with Environmental Legislation Ecuadorian and according to the Ecuadorian NTE INEN 1 108:2006 Standard. The hardness is 20 mg / l CaCO3, for that reason the water is corrosive, sometimes the water affected the skin, cookware corrosion ….